Забезпечення ступеня точності циліндричних зубчастих коліс під час їх зубооброблення в умовах автоматизованого виробництва - Гуліда, Е. М.; Жаровський, А. М. (Видавництво Національного університету «Львівська політехніка», 2004)
Considered question of exactness degree guaranteeing of cylindrical rack-wheels attached to their toothing in conditions of automated production with use of mathematical modeling of toothing operations and use of experiments results attached to spurmilling of cylindrical rack-wheels by helical millers.